2017
DOI: 10.1016/j.nbt.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the feruloyl esterase gene family of Aspergillus niger by characterization of a feruloyl esterase, FaeC

Abstract: A feruloyl esterase (FAE) from Aspergillus niger N402, FaeC was heterologously produced in Pichia pastoris X-33 in a yield of 10mg/L. FaeC was most active at pH 7.0 and 50°C, and showed broad substrate specificity and catalyzed the hydrolysis of methyl 3,4-dimethoxycinnamate, ethyl ferulate, methyl ferulate, methyl p-coumarate, ethyl coumarate, methyl sinapate, and methyl caffeate. The enzyme released both ferulic acid and p-coumaric acid from wheat arabinoxylan and sugar beet pectin (up to 3mg/g polysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 47 publications
4
57
0
2
Order By: Relevance
“…Both induced LPMOs have been predicted to act on cellulose (Borin et al ) and one of them (NRRL3_3929) has been suggested to be regulated by AraR (Gruben et al ). The transcriptional profile of the FAE encoding genes correlated with previous observations (de Vries et al ; Dilokpimol et al ). Ferulic acid can be linked to l ‐arabinose in xylan, which could explain why the other xylanolytic genes were also induced by ferulic acid.…”
Section: Discussionsupporting
confidence: 88%
“…Both induced LPMOs have been predicted to act on cellulose (Borin et al ) and one of them (NRRL3_3929) has been suggested to be regulated by AraR (Gruben et al ). The transcriptional profile of the FAE encoding genes correlated with previous observations (de Vries et al ; Dilokpimol et al ). Ferulic acid can be linked to l ‐arabinose in xylan, which could explain why the other xylanolytic genes were also induced by ferulic acid.…”
Section: Discussionsupporting
confidence: 88%
“…P. pastoris transformants containing FAEs from Aspergillus species, Ceriporiopsis subvermispora, and Galerina marginata were grown according to previous reports [26,28,30,32]. Induction was done for 96 h at 28 • C with methanol being supplemented to 0.5% (v/v) every 24 h. Culture supernatants were harvested (4000× g, 4 • C, 20 min), filtered (0.22 µm; Merck Millipore, Darmstadt, Germany), concentrated (10 kDa cut off; Merck Millipore, Germany), and stored at −20 • C prior to further analysis.…”
Section: Production Of Enzymes In Pichia Pastorismentioning
confidence: 99%
“…As an example case to confirm the consistency of the substrate specificity within the subfamilies of CE1, we heterologously expressed and characterized A. terreus FaeD. This enzyme is a member of subfamily 5 (Figs and S1), which also contains the recently characterized AnFaeC from A. niger (Dilokpimol et al ., ) in a different branch. The Aspergilli appear to have abundant numbers of putative FAE‐encoding genes, and previously clear differences have been reported between the three characterized FAEs from A. niger (de Vries et al ., ; Dilokpimol et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…These include N. crassa FaeD (Crepin et al ., ), A. sydowii FaeC and FaeD1 (Dilokpimol et al ., ), A. nidulans FaeC (Debeire et al ., ) and A. niger FaeC (Dilokpimol et al ., ), as well as AtFaeD characterized in this study, thus supporting that CE1 subfamily 5 is also a FAE subfamily. In addition to the artificial FAE substrates, several of the functionally characterized subfamily 5 enzymes have also been shown to release ferulic acid from natural plant biomass substrates, such as wheat arabinoxylan (WAX) and SBP (Crepin et al ., ; Dilokpimol et al ., ), or hydrolyse feruloylated oligosaccharides (Debeire et al ., ).…”
Section: Resultsmentioning
confidence: 99%